2019
DOI: 10.56093/ijas.v89i8.92853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus fertilisation on growth, yield and quality of pea (Pisum sativum)

Abstract: In the present study, experiments were undertaken during 2016-2017 to examine the effect of phosphorus application on pea (Pisum sativum L.) cv. Arkel and Azad P-1. Four levels of phosphorus (0, 60, 90, 120 kg/ha) keeping the N at K dose constant at 25 and 50 kg ha-1 respectively with 3 replications were used in two way factorial analysis. The effects of different doses of phosphorus were judged on growth, yield and quality attributes. Evaluation of comparative performance of pea varieties Arkel and Azad P-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Pea varieties respond differently to fertilization [ 23 , 28 ] and environmental conditions [ 2 ]. The main traits that determine the level of adaptability in peas are a high harvest index, good ripening, disease resistance, resistance to shatter, high potential yield, seed weight, and seed number per pod [ 25 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pea varieties respond differently to fertilization [ 23 , 28 ] and environmental conditions [ 2 ]. The main traits that determine the level of adaptability in peas are a high harvest index, good ripening, disease resistance, resistance to shatter, high potential yield, seed weight, and seed number per pod [ 25 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khangjarakpam et al [14], also observed similar results in marigold with application of GA 3 in China aster. Husain et al [15] also observed increase in seed yield with GA 3 application in pea.…”
Section: Introductionmentioning
confidence: 85%
“…Ismail (2016) and Badr and Fayed (2020) reported, fertilization with a combination of N, P and K at different percentages has a positive impact on pod quality traits such as pod length, diameter, weight and seeds per pod. W here, phosphorus promotes reproductive growth, leading to higher pod yield, longer pods, more grains and more pods per plant Husain et al (2019) and potassium is crucial for plan t energy status, assimilate transloc ation and maintenance of tissue water relations. The results are in conformity with Akter et al (2020).…”
Section: Effect Of Weather Conditionsmentioning
confidence: 99%